False positive and specificity of anti-HIV-1 EL/SA kit : features, causative factors, and its confirmatory test - Suwarso, Suwarso (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1995)
As screening tool for HIV-1 infection, anti HIV-1 ELISA kit with high sensitivity was proved to be very efficient. Because of its high sensitivity, the use of the kit to screen HIV-1 infection in low risk individuals or in seroprevalence study in population of non-endemic area will reduce its specificity. Therefore, there will be many false positive results which, in turn, will give psychosocial and economical impact to the individuals In question. To evaluate false positive results and specificity of anti HIV-1 kit, 1028 normal individuals with low risk of HIV-1 infection were studied. All positive results from HIV-1 ELISA kit confirmed with confirmative ELISA and Western-blot analysis. The results showed that HIV-1 ELISA kit gave false positive results of 1.17% and specificity of 98,38%. Ninety one point seven percent of false positive results had low-ODs ( 2 ODBP) and poor reproducibility value (8,3%). Seventy five percent of these false positive were from individuals aged 1-15 years and not related to gender as well as socioeconomical status. The probable causes of false positive results are endogenous factors in sera samples such as alteration of density of sera during storage, the presence of anti-granulocyte, anti-HLA, antibody to cultured lymphocyte h9/lllb, and polyclonal hyperglobulinemia. Confirmatory ELISA with antigen control had the same sensitivity and specificity as Western-blot. Therefore, ELISA with antigen control can be used for confirmation test of positive or questionable results obtained from anti HIV-1 ELISA. The kit is cheaper and faster, and is very practical to use, especially in laboratories equipped with ELISA system.Key Word : anti-HIV-1 ELISA - specificity - false positive - confirmatory ELISA - Western-blot.